THE IMPLEMENTATION OF DIRECT METHOD TO IMPROVE STUDENTS’ ABILITY IN SPEAKING - Nurhayati Sitorus; Harpen Silitonga (STKIP Siliwangi, 2018)
The purpose of this study is to investigate students’ ability in speaking before and after using Direct Method in learning English. The method in this research was experimental quantitative method by using quasi experimental design with one group pretest-posttest model. The design only saw students’ achievement in speaking before and after using Direct Method. The object of the research was English Department students. They were randomly selected. The technique of collecting the data was done through observation and the data were gotten from the students when they did oral communication. The instrument in this research was oral test. The result of this study shown that the use of Direct Method could improve students’ ability in speaking. It was proved from the students’ average was higher after using Direct Method. The data in this research had normal distribution. Based on data analysis by using T-test was gotten that tcount = 7,14 at the significant level = 5% and dk (n-1) = (40-1) =39 was gotten ttable = 1,82. So, tcount > ttable. It proved that Ho was rejected and Ha was accepted. It’s meant that there was a significant difference between students’ ability before and after implementing Direct Method.